Pregnancy after liver transplantation following idiopathic subacute liver failure: A multidisciplinary Approach - Igbokwe, Nnadozie; Ugwoke, Sunday P.; Sharma, Meenu (European Journal of Applied Sciences, 2021)
Liver transplantation (LT) is the definitive treatment for end stage liver disease. Liver cancer, viral hepatitis and alcohol related liver diseases are the common causes for transplantation. The outlook for pregnancy in post-transplant patient is generally good although they are considered higher risk than the general population. As far back as 1978, the first successful pregnancy in a liver transplant patient was reported with as many as 12 pregnancies per year occurring in liver transplant recipients in the UK. We present a 27-year old primigravida who had liver transplant when she was 9 years old due to idiopathic subacute liver failure. She conceived spontaneously and had an unremarkable multidisciplinary antenatal care with induction of labour and vaginal delivery at 38 weeks gestation with good outcomes. This case highlights the importance of multidisciplinary team (MDT) management and follow-up in liver transplant patients.